Exercice at altitude – historical remarks (Fiep Bulletin - online, 2015)
The first to realize that animal life depends upon the availability of oxygen were Lavoisier, Priestley, and Scheele. In 1774, Lavoisier demonstrated that air contains a “pure” and a “noxious” portion; that candles burn and mice live only in the former. And that mice live only in the former; and that during exercise increased amounts of oxygen – the term was introduced by Lavoisier – are required.